O princípio do poluidor-pagador e o meio ambiente de trabalho - Torres, Rodrigo Araújo (2012)
As the beginning of the industrial process, on the second half of the 18th Century, due to the Industrial Revolution, which arise initially in England, triggering the manufacturing by mass production. New technology applied on machinery capable of accelerating the making of new products released a good feeling on people, not only because of consume potential, but also due to the great amount of industrial products, at affordable prices, giving cause to scarcity of natural resources and, also, afflicted serious problems to workers, for not having any ideas on the risks incurred of working with machinery applied for production, completely unconnected with the safety of their operators. A different range of conflicts developed branches of law regarding to the present research: labor law and environmental law. Along the deployment of environmental law, from the United Nations Conference in 1972, in Stockholm/ Sweden, and in Rio de Janeiro/ Brazil, in 1992, as an autonomous subject within the law, with its specificities and connection with other legal disciplines, has noticed that the concepts and standards usually thought of as genuinely labor may actually be rules and concepts applications of environmental law. This research aims to conduct this analysis, checking whether the additional health and safety arising from the unhealthiness of the Polluter Payer Principle, and the provision of Personal Protective Equipment. The 1988 Federal Constitution provides the legal basis for both branches of Law in question: in its 7th article it bases workers' rights, whereas the article 225th, provides that an ecologically balanced environment is essential to a healthy quality of life. Since the environment is one and indivisible, the work environment is inserted in this context. Also, it appears that life referred to the article under discussion is human, marking thus the philosophical reasoning followed in this study, which is anthropocentric. The Polluter Payer Principle, disposed in § 3rd of Article 225 of FC/88, searches environmental pollution in the production process costs, avoiding the implementation of such to society. We conclude that the Polluter Pays Principle is applied in labor law, perceiving its implementation in insalubrities’ premiums and the obligation of PPE use as well as a must be revised values and accumulation of bonuses materializing up the Principle of Environmental Law presented, by internalizing the costs of environmental pollution more widely than now taken.